Larval description of Salween Frog Hoplobatrachus salween (Anura: Dicroglossidae) from Northwestern Thailand - Chuaynkern, Chantip; Thongproh, Prapaiporn; Waiprom, Likhit; Makchai, Sunchai; Duengkae, Prateep; Duangjai, Sutee; Chuaynkern, Yodchaiy (Agriculture and Natural Resources, 2023)
Importance of the work: Existing knowledge lacks description of tadpoles of Hoplobatrachus salween. The current study filled this knowledge gap by providing a detailed description of external and buccal anatomy. Objectives: To describe the external morphology and buccal anatomy of the tadpoles of H. salween. Materials & Methods: Tadpoles were described based on six specimens (THNHM 26833.1–6) collected in Salawin National Park, Mae Sariang, Mae Hong Son province, northwestern Thailand. Identification was based on Thongproh et al. (2022). External morphological description was based on THNHM 26833.2. Buccal description was based on images from scanning electron micrographs of THNHM 26833.2. Results: The tadpoles were large-sized (total length 48.1–63.2 mm, stages 37–39), body ovate, tail musculature moderate, oral disc moderate-sized. Keratodont row formula = 2:2+2/3+3:2 (stage 37) and 2:3+3/3+3:2 (stage 39–40), biserial rows at 1st upper labial teeth row and 2nd–5th lower labial teeth rows), single row at 2nd–5th upper labial teeth rows, three rows at 1st lower labial tooth row. The prenarial arena was wide with a large medial keratinized conical knob. Main finding: The results have provided the first description of the external morphology and buccal anatomy of tadpoles of H. salween. This work has added knowledge on buccal anatomy, which is insufficient in members of Hoplobatrachus spp